A Turn-On Fluorescence Sensor Based on Guest-Induced Luminescence Ru(bpy)32+@UiO-66 for the Detection of Organophosphorus Pesticides - Jun Li; Jianlan Deng; Qian Tao; Chenyu Yan; Yuxuan Liu; Jianxiao Yang; Zhong Cao (Molecules)
Luminescent metal–organic frameworks (MOFs) are used for the detection of organophosphorus pesticides (OPs) due to their large surface area and pore volume as well as their special optical properties. However, most self-luminescent MOFs are not only complex to synthesize and unstable in water but also feature a “turn-off” sensing system, which has highly restricted their practical applications in OP detection. Herein, a “turn-on” fluorescence sensor based on the guest-induced luminescence MOF Ru(bpy)32+@UiO-66 was constructed, which realized the sensitive detection of OPs through a dual-enzyme system for the first time. Compared with self-luminescent MOFs, Ru(bpy)32+@UiO-66 was not only more easily synthesized but also had higher chemical and photostability in water. In this strategy, by means of the hydrolysis of AChE and ChOx, H2O2 will be produced, which can oxidize Fe2+ to Fe3+, thereby quenching the fluorescence of Ru(bpy)32+@UiO-66. In the presence of OPs, the activity of AChE can be inhibited, resulting in the inability to generate H2O2 and Fe3+, which will turn on the fluorescence signal of Ru(bpy)32+@UiO-66. As a result, the Ru(bpy)32+@UiO-66 sensing system not only had high sensitivity for OPs detection but also possessed a satisfactory detection recovery rate for parathion-methyl in real samples, which provides a new approach for OP detection in food safety as well as environmental monitoring.